Persistence of thyroid microsomal and thyroglobulin antigens in primary cultures of human thyroid epithelium - Ghose, T. (1969)
The changes in the amount and distribution of thyroglobulin and thyroid `microsomal' antigens were studied in primary explant and monolayer cultures of human thyroid epithelium which were alive for about 60 days. Both explant and monolayer cultures produced thyroglobulin in vitro at all times during the 60-day period of observation. However, the number of cells containing the thyroid `microsomal' antigen and the amount of antigen in individual cells both diminished though the antigen was detectable in a proportion of viable cells in all cultures at all times during the 60-day period of observation of this report.